2006
DOI: 10.1183/09031936.00029206
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin in the treatment of RSV bronchiolitis: a double-blind, randomised, placebo-controlled trial

Abstract: Respiratory syncytial virus (RSV) bronchiolitis is the most common lower respiratory tract infection in infancy. To date, there is no effective therapy for RSV bronchiolitis.In order to investigate the efficacy of clarithromycin in the treatment of RSV bronchiolitis, the present authors conducted a randomised, double-blind, placebo-controlled trial comparing clarithromycin with placebo in 21 infants with a diagnosis of RSV bronchiolitis. The infants were randomised to receive clarithromycin or placebo daily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 50 publications
6
130
1
6
Order By: Relevance
“…Clarithromycin was proposed to have a possible immunomodulatory effect. More well planned studies to clarify role of macrolides in acutebronchiolitis are required 16 . In children with bronchiolitis and fever, the risk of secondary bacterial infection is low, therefore, routine use of antibiotics is not warranted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clarithromycin was proposed to have a possible immunomodulatory effect. More well planned studies to clarify role of macrolides in acutebronchiolitis are required 16 . In children with bronchiolitis and fever, the risk of secondary bacterial infection is low, therefore, routine use of antibiotics is not warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Corticosteroids have not clearly been shown to be of significant benefit in improving the clinical status of patients with bronchiolitis.However, in some countries they are used routinely 13 . Antibiotic is commonly used in children with bronchiolitis, but should not be indicated unless bacterial infection is suggested [15][16][17][18] . .…”
Section: Resultsmentioning
confidence: 99%
“…In a double-blind, randomised, placebo-controlled trial, TAHAN et al [107] evaluated the efficacy of clarithromycin given daily for 3 weeks at a dose of 15 mg?kg -1 in infants aged ,7 months hospitalised for RSV bronchiolitis. Nine subjects were excluded from analysis due to corticosteroid use, leaving 12 in the clarithromycin group and nine in the placebo group.…”
Section: Respiratory Viral Infectionsmentioning
confidence: 99%
“…In 1966, FIELD et al [140] reported no positive effect of broad-spectrum b-lactam antibiotics on the course of disease in 52 patients. In 2007, TAHAN et al [141] reported that macrolides reduced length of hospitalisation. A Dutch RCT did not show that azithromycin reduces the duration of hospitalisation [142].…”
Section: Leukotriene Receptor Antagonistsmentioning
confidence: 99%